Divergent nanostructures from identical ingredients: unique amphiphilic micelle template for polyaniline nanofibers, tubes, rods, and spheres - Anilkumar, P.; Jayakannan, M. (Macromolecules, 2008)
Here, we report a unique soft templating approach based oil all in-built amphiphilic azobenze-nesulfonic acid for tuning various types of polyaniline nanomaterials Such as fibers, rods, spheres, and tubes. The dopant molecule is freely soluble in water, and DLS measurements Of the resultant Solution revealed that it forms spherical micelles of diameter similar to 4.29 nm. The addition of aniline induces self-organization in the dopant micelles which produce micrometer-sized cylindrical aggregates or layerlike assemblies depending upon the aniline/dopant composition in the feed. In the emulsion route. the oxidation of these cylindrical or layerlike micelle aggregates produce nanofibers and nanotubes, respectively. The dilution of thick emulsion microaggregates led to the formation Of uniformly distributed small 175 nm aggregated micelles. which template for the nanorods (dilution route). Alternatively, the dopant micelles form spherical shape aggregates with oxidizing agent ammonium persulfate (APS) in water. Aniline molecules diffuse through the organic/aqueous interface and get absorbed at these spherical aggregates, and subsequent chemical oxidation produces exclusively polyaniline nanospheres (interfacial route). The mechanism of the polyaniline nanomaterials formation was investigated by dynamic light scattering (DLS) and high-resolution transmission electron microscopy (TEM). DLS studies of the polymerization mixtures in water evident for the formation of micrometer range aggregates. TEM analysis confirmed the shape of the template as cylindrical, cylindrical + spherical, and spherical geometry for the complexes of dopant with aniline and APS in the emulsion, dilution, and interfacial routes, respectively. The amphiphilic nature of the dopant solubilizes the nanomaterials in water and organic solvents, and the optical properties of nanomaterials were studied in various solvents by UV-vis spectroscopy. The wide-angle X-ray diffraction Studies confirmed the appearance of a new peak at lower angle (d = 13.6 angstrom) corresponding to the highly crystalline and ordered polyaniline nanomaterials. The solid-state properties of the nanomaterials were found to he highly dependent on the size and shape of polymerization templates employed for the synthesis.